A rare case series of bilateral pneumothorax among adult COVID-19 patients reported at a tertiary care hospital in Mizoram, India - Sailo, Lalnuntluanga; Ralte , Wendy L; Varte, Zorinsangi; Sailo, Lalnunmawii; Zodinpuia, Micky; Khiangte, Zorinpuii; Anusuya, Ganesh Shanmugasundaram (Asian Journal of Medical Sciences, 2023)
Apart from routine symptoms such as fever, cough, sore throat, myalgia, and dyspnea in severe form of Coronavirus Disease-2019 (COVID-19) infection, very rarely patients can develop worsening of dyspnea due to bilateral pneumothorax. The present case series is about five adult patients, of age ranging from 39 to 57 years, who developed bilateral pneumothorax during their stay in the hospital. All the cases were reported between May 2021 and October 2021 and were tested positive for COVID-19 by reverse transcriptase polymerase chain reaction. Out of five adults, three patients were males and were two females. All the patients were assessed with quick sequential organ failure assessment (q SOFA) score on admission and then monitored by SOFA Score. On admission, baseline contrast enhanced computer tomography chest was done for three patients, and chest radiography for one patient all showing features of moderate to severe COVID-19 pneumoniae. One patient with q SOFA Score of 3 on admission required immediate invasive mechanical ventilatory support with ultrasonogram chest immediately performed showing bilateral pneumothorax. Patients were started on remdesivir, dexamethasone, low molecular weight heparin or unfractionated heparin, tocilizumab, and antibiotics. Subsequently, during the course of stay in the hospital, rest of the four patients developed symptoms of pneumothorax and emergency bedside chest ultrasonography showed the typical barcode or stratosphere sign confirming bilateral pneumothorax. All the patients were managed with bilateral chest intercostal water seal drainage intercostal drain tube and invasive mechanical ventilation. Fraction of Inspired Oxygen (FIO2), and other ventilatory settings were adjusted depending on daily arterial blood gas findings. Attempts to wean off from ventilatory support and extubation were successful for two patients, whereas three patients did not survive. In this case series, we will be presenting about those five cases of bilateral pneumothorax in COVID-19 patients reported at a tertiary care hospital in Mizoram, India.